Impact of Natural Pozzolan And The Degree of Circularity of Aggregates on The Thickness, Strength and Durability Of ITZ in Concrete ( Modeling and Experimentation) - Mezghiche, Bouzidi; Belkadi, Ahmed Abderraouf; Loumachi, Lazhar (Graduate School of Universitas Syiah Kuala, 2023)
The interfacial transition zone (ITZ) significantly negatively impacts the structural performance of concrete. This negative impact can be ameliorated by introducing mineral additions into the concrete. In this study, different forms (degree of circularity) of coarse aggregates and three contents (10%, 15%, and 20%) of mineral addition (natural pozzolan) were used to prepare ordinary concrete. This article aims to determine the optimal and effective mixture (the best form of aggregate and addition). This article aims to determine the optimal and efficient mixture (the best form of aggregate and addition) based on mechanical (compressive strength) and chemical (immersion in 3.5 % H2SO4 solution) tests. Furthermore, the effect of the interaction between the aggregate and the modified cementitious matrix was analyzed and discussed using the scanning electron microscope (SEM). The results show that adding 20% pozzolana improves the aggregate/matrix transition zone, making it possible to develop a maximum compressive strength at 60 days (51 MPa). In addition, the effect of mineral additions varies depending on the shape of the coarse aggregate. Thus, effective numerical modeling of the compressive strength is based on the full factorial design approach, considering the degree of circularity of the coarse aggregates and the pozzolan content.